2001
DOI: 10.1046/j.1529-8817.2001.037004604.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYLOGENETIC RELATIONSHIP AMONG VARIOUS STRAINS OF DUNALIELLA (CHLOROPHYCEAE) BASED ON NUCLEAR ITS rDNA SEQUENCES

Abstract: Phylogenetic analyses of 15 strains representing 8 taxa of Dunaliella ( D. salina, D. bardawil, D. pseudosalina, D. tertiolecta, D. parva, D. viridis, D. peircei , and D. lateralis ) belonging to both subgenera and all sections of the genus were carried out using the sequences of the nuclear rDNA spacers (internal transcribed spacer [ITS-1 ؉ ITS-2]). The ITS data agreed with the traditional data in that D. lateralis (from subgenus Pascheria ) is only distantly related to the seven taxa of the subgenus Dunaliel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 36 publications
3
55
2
Order By: Relevance
“…González et al (1998) showed a low intraspecific genetic variability in strains from different countries. However, an important correspondence among intraspecific genetic variability and morphological and physiological behaviour has been found in D. salina, though the morphologic traditional criteria of taxonomical classification present diverse limitations (Cifuentes et al 2001;Gómez and González, 2001;González et al 2001). In the present work, it can be underlined the wide morphological and physiological variation found among native strains isolated from various saltworks in close geographical vicinity.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…González et al (1998) showed a low intraspecific genetic variability in strains from different countries. However, an important correspondence among intraspecific genetic variability and morphological and physiological behaviour has been found in D. salina, though the morphologic traditional criteria of taxonomical classification present diverse limitations (Cifuentes et al 2001;Gómez and González, 2001;González et al 2001). In the present work, it can be underlined the wide morphological and physiological variation found among native strains isolated from various saltworks in close geographical vicinity.…”
Section: Discussionmentioning
confidence: 63%
“…However, carotenoid productivity from D. salina is fundamentally determined by other parameters, such as cellular division rate and biomass production (Hejazi and Wijffels, 2003). This approach to the potential productivity of the strains we propose is more comprehensive than the simple evaluation of carotenoid cellular contents because as well as this variable, we include other parameters such as chlorophyll/carotenoid ratio, cellular size and complexity, which are related with growth rate in D. salina (Gómez et al 1999;Giordano, 2001;Gómez and González, 2001). With this new approach to select carotenoid hyperproducing strains of D. salina it is possible to directly estimate the potential growth rates and carotene productivity in complex samples with different strains.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequence comparisons) could show that some accepted approaches to delineating species of protists (e.g. morphogenesis) combined different taxonomic units (Gonzalez et al 2001). It is therefore not surprising to observe more accurate patterns of distribution with more constrained parameters for phylogenic delineation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have encompassed the 18S rRNA genes and the internal transcribed spacer regions, ITS and have been based on gene sequence comparisons as well as on restriction fragment length polymorphism studies (Gomez and Gonzalez, 2001;Assunção et al, 2012). Little correlation was found between the molecular data and the traditional morphological-physiological attributes to delineate species within the genus Dunaliella (González et al, 1999(González et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%